Initiating early palliative care for older people with advanced cancer and its barriers. Issue 1 (March 2022) - Bugaj, Till J.; Oeljeklaus, Lydia; Haun, Markus W.
Abstract : Purpose of review: Early palliative care (EPC) is known to generally improve both health-related quality of life (QoL) and symptom intensity at small effect sizes. However, it is unclear whether EPC is effective in older people, a population that is notoriously unaccounted for. This review summarizes the recent evidence concerning the efficacy of EPC in older patients with advanced cancer and delineates existing barriers to accessing respective services. Recent findings: The search for studies published in MEDLINE from January 2020 to September 2021 yielded six relevant records. Data from a recent feasibility trial and subgroups from larger randomised trials point to a somewhat lesser decline in QoL for patients undergoing EPC compared to those receiving treatment as usual. However, enrolling older patients in such trials remains a major challenge mostly due to them feeling too ill to participate. Summary: For older patients, the efficacy of EPC, like many other medical interventions, has hardly been studied so far. Existing work yielded several specific barriers for older patients to access this type of care. Future research should prioritize efficacy trials of EPC tailored to the needs of older patients enabling clinicians to enter truly evidence-based shared decision-making with their patients.